Validity of Pulmonary Tuberculosis Control Success Index (TBCSI) Instrument - Anwar, M. Choiroel; Budiono, Irwan; Nisa, Alfiana Ainun (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
The target for reducing the incidence of TB in 2019 was 245/100,000 population. However, the national TB incidence is at 321/100,000 population, implying that mapping the performance of PHC is inevitable to help accelerate control efforts. This study aims to develop an instrument, the “TB control success index” (TBCSI), and measure the TBCSI achievement of all PHC in Semarang City. Quantitative research was conducted to construct the TBCSI instrument, and a validated TBCSI instrument was used to measure the TBCSI of all PHC individuals in Semarang City. The validity test showed Aiken’s V coefficient for each TBCSI instrument question item > 0.92. Furthermore, the TBCSI results at the Semarang City showed an average of 0.9332. The average index of the 6 TBCSI dimensions were 0.8959 (program leadership dimension); 0.8495 (TB service access dimension); 0.9667 (risk factor control dimension); 0.9797 (increase in partnership dimension); 0.9240 (increasing community independence dimension); and 0.9874 (management strengthening dimension). The TBCSI instrument was proven valid to measure the success rate of PHC in implementing TB control programs. Therefore, the TBCSI of all PHCs in Semarang City was included in the good category.